The Transformation of the Dilan 1991 Novel by Pidi Baiq into the Dilan 1991 Film by Fajar Bustomi (A Study of Pamusuk Eneste's Ecranization) - Magfirah Magfirah; Mahmudah Mahmudah; Andi Agussalim AJ (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to describe the form of intertextual relationship between the Dilan 1991 Novel and the Dilan 1991 Film and the process of ecranization of the novel into the Dilan 199 film. This research is descriptive qualitative. The results of this study indicate that in the form of intertextual relationships the novel and Dilan 1991 film are permutative by comparing, aligning, and contrasting. The comparison includes characters and characterizations as well as settings in novels and films. Similarities include themes, plots, characters & characterizations, point of view, and messages. The contrast that occurs is that the Dilan 1991 Novel by Pidi Baiq is a hypogram of the Dilan 1991 Film by Fajar Bustomi called affirmation. The process of ecranization of the novel into the Dilan 1991 film went through three stages, namely reduction, addition, and change of variation. The downsizing includes Milea telling the story of meeting Dilan, the story about Dilan with Wati and Piyan, Beni visiting Milea's house in Bandung, Pak Dedi and Milea going home together, the Reformation Event, and Milea's current condition. Additions to the film include Dilan visiting Milea's house. Varied changes in the film include changes in story visualization so that the description of the storyline is more variedKeywords: Novel, Film, Ecranization